RELATIONSHIP BETWEEN LEVEL OF EDUCATION AND POST-STROKE COGNITIVE STATUS IN HOSPITAL-BASED ISCHEMIC STROKE SURVIVORS - Harahap, Herpan Syafii; Indrayana, Yanna; Putri, Setyawati Asih (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Post-ischemic stroke cognitive decline is significantly affecting the quality of life of its survivors. Its prevalence was about 7.5-72% which was mostly determined by the existing of vascular risk factors and cognitive reserve of the subjects. Level of education is one of determinants of cognitive reserve, a factor that affect the susceptibility of subjects to cognitive decline after experiencing ischemic stroke-related neuronal damage. Since level of education is protective for cognitive function, the intervention on it can reduce the occurrence of cognitive decline.Objective: To investigate the relationship between level of education and cognitive status among hospital-based ischemic stroke survivors.Methods: This cross-sectional study involved post-ischemic stroke outpatients in two hospitals. The data collected in this study were demographic data, including level of education, and clinical data as well. The level of education was categorized into â‰¥12 years and <12 years groups. Cognitive status was assessed using Montreal Cognitive Assessment in Indonesia version (MoCA-Ina) and subjects with score of 26-30 were normal. The relationship between level of education as well as clinical data and cognitive status were analyzed using chi-square test.Results: There were 166 subjects eligible for this study (n=166). The mean age of subjects was 58 years and 68.67% of them were male. Cognitive decline were found 80.12% of subjects (n=133). The level of education was significantly associated with cognitive status of the subjects and hypertension as well.Conclusion: The level of education had significant relationship with cognitive decline in the hospital-based population of ischemic stroke survivors.